2013
DOI: 10.1007/s11606-013-2571-5
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Patients with Low Socioeconomic Status During the Post-Hospital Transition

Abstract: BACKGROUND:Patients with low socioeconomic status (low-SES) are at risk for poor outcomes during the posthospital transition. Few prior studies explore perceived reasons for poor outcomes from the perspectives of these high-risk patients. OBJECTIVE: We explored low-SES patients' perceptions of hospitalization, discharge and post-hospital transition in order to generate hypotheses and identify common experiences during this transition. DESIGN: We conducted a qualitative study using indepth semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 37 publications
1
91
0
Order By: Relevance
“…This 18 and many readmissions are not easily attributable to a single cause. 1,19 Therefore, even if the three domains of the CTM-3 were addressed equally for patients with PCI and CABG, their post transition experiences and ultimate reasons for readmission could vary greatly. Although our study generally supports the association between the CTM-3 score and readmission, it should be interpreted with caution, and the association should be validated on a large scale, at the hospital level in future studies.…”
Section: And Readmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…This 18 and many readmissions are not easily attributable to a single cause. 1,19 Therefore, even if the three domains of the CTM-3 were addressed equally for patients with PCI and CABG, their post transition experiences and ultimate reasons for readmission could vary greatly. Although our study generally supports the association between the CTM-3 score and readmission, it should be interpreted with caution, and the association should be validated on a large scale, at the hospital level in future studies.…”
Section: And Readmissionmentioning
confidence: 99%
“…Poor care coordination during this time increases the risk for potentially avoidable hospital readmissions. 1 Such readmissions place a tremendous burden on patients and families and cost the US health system approximately $12 billion annually. 2 Unlike other risk factors for readmission, such as race, sex and age and prior hospitalization, 3 poor transitions of care can be remediated with improved care management.…”
Section: Introductionmentioning
confidence: 99%
“…7 Kangovi et al used in-depth interviews to explore the perspective of patients of low SES on their experience of discharge from the medical or cardiac services of the hospital and the transition to a non-acute setting. The study reveals many ways that we can better address the needs and concerns of our most vulnerable patients making the transition from the hospital to home.…”
mentioning
confidence: 99%
“…This longitudinal qualitative study detailing the lived experience of discharge extends our knowledge of challenges faced by patients during the posthospital transition, 2 and further elucidates the differences between patients' expectations and assessments of their resources and goals, and their actual abilities and priorities on discharge. Despite substantial assistance, including housing, food assistance, and case management, Chan Carusone et al found that the exigencies of day-to-day existence exceeded the patients' capacities to sustain themselves outside the hospital.…”
mentioning
confidence: 85%